Coordinate Interleaved Orthogonal Design With Media-Based Modulation - Yildirim, Ibrahim; Basar, Ertugrul; Altunbas, Ibrahim (Institute of Electrical and Electronics Engineers (IEEE), 2021)
In this work, we propose a new multiple-input multiple-output (MIMO) concept, which is called coordinate interleaved orthogonal design with media-based modulation (CIOD-MBM). The proposed two novel CIOD-MBM schemes provide improved data rates as well as diversity gain while enabling hardware simplicity using a single radio frequency (RF) chain. Moreover, using the equivalent channel model, a reduced complexity can be obtained for maximum likelihood (ML) detection of the proposed system. Using computer simulations, it is shown that CIOD-MBM schemes provide remarkably better performance against the conventional MBM and CIOD systems.
Keywords: Coordinate interleaved orthogonal design; Signal Processing (eess.SP); Coordinate interleaved orthogonal design; Index modulation; Media-based modulation; Space-time coding; Engineering; Telecommunications; Transportation; Transportation; Space-time coding; Index modulation; Engineering; Telecommunications; FOS: Electrical engineering, electronic engineering, information engineering; Electrical Engineering and Systems Science - Signal Processing; Media-based modulation